The Effect Of Corporate Governance Mechanisms On Financial Distress - Liyanita Dewi Kurnia; Christina Dwi Astuti (Al-Makki Publisher, 2023)
In this study, the authors are interested in examining how institutional ownership, independent commissioners and audit committees influence financial distress. The population of all manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021 totaling 106 samples. According to the criteria required in this study, only 19 companies were sampled for 2018 to 2021. The results showed that the Board of Directors has a positive influence significant effect on financial distress, the proportion of independent commissioners has no significant effect on financial distress, audit committee size has no significant effect on financial distress, and institutional ownership has a significant negative effect on financial distress